2017
DOI: 10.1016/j.ibror.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Interneurons secrete prosaposin, a neurotrophic factor, to attenuate kainic acid-induced neurotoxicity

Abstract: HighlightsPS increased mainly in the axons of PV positive interneurons after kainic acid (KA) injection.Electron microscopy revealed PS containing vesicles in PV positive axons.PS is secreted with secretogranin from synapses.The increased PS in the interneurons was due to increases in PS + 0, as in the choroid plexus.Interneurons produce and secrete intact PS around the hippocampal pyramidal neurons to protect them from KA neurotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…PSAP is suggested to be an essential neurotrophic factor since its secretion stimulates proliferation and maturation of immature neurons in the hippocampus DG, as well as provides protection against apoptosis. It was reported that deficiency of PSAP precedes massive neuronal loss in neurotoxic environments (Morishita et al, 2014 ; Nabeka et al, 2017 ).…”
Section: Focus On Msc-derived Exosomes and Their Role In Neuroplasticmentioning
confidence: 99%
“…PSAP is suggested to be an essential neurotrophic factor since its secretion stimulates proliferation and maturation of immature neurons in the hippocampus DG, as well as provides protection against apoptosis. It was reported that deficiency of PSAP precedes massive neuronal loss in neurotoxic environments (Morishita et al, 2014 ; Nabeka et al, 2017 ).…”
Section: Focus On Msc-derived Exosomes and Their Role In Neuroplasticmentioning
confidence: 99%
“…Prosaposin (PSAP) is also a lysosomal regulatory protein with significant neuroprotective properties [3638]. Recent studies have shown biochemical interactions between PGRN and PSAP, with these interactions affecting the trafficking of these proteins to lysosomes [3941].…”
Section: Introductionmentioning
confidence: 99%
“…PSAP deficiencies in mice led to significant impairment of PGRN trafficking to lysosomes but increased circulating levels of PGRN [41]. Experimental models of neuronal injury resulted in increased levels of PSAP in neurons and microglia [38, 42, 43]. The interactions of PGRN and PSAP are complex as both PSAP reduction and overexpression resulted in elevated levels of extracellular/secreted PGRN in different cellular models [4].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of fewer injured neurons and more healthy neurons in the PS18-injected rats indicated that PS18 rescues CA1 neurons from KA-induced degeneration. The detection of higher levels of PSAP in PV-positive GABAergic inhibitory interneurons and their axons around pyramidal neurons suggested the axonal transport of PSAP [24,25] (Figure 1h-i). Similarly, PSAP was strongly expressed in the Purkinje cells and interneurons of the cerebellum of KA-injected rats [26].…”
Section: Psap Rescues Neurons From Damage Induced By Neurotoxic Agentsmentioning
confidence: 95%